The costs and funding of civil litigation: a comparative perspective - Hodges, Christopher J. S. (Hart, 2010)
This book contains the first major comparative study of litigation costs and methods of funding litigation in more than 30 jurisdictions. It was linked with the most comprehensive review of costs ever carried out in England and Wales by Lord Justice Jackson in 2009 and benefited from the assistance of leading practitioners around the globe. The study analyses the principles and rules that relate to paying courts, witnesses and lawyers, and the rules on cost shifting, if any. It also notes the major ways in which litigation can be funded, identifying the global trend on contraction of legal aid
Includes bibliographical references and index
Keywords: Rechtsvergleich; Kostenrecht; Zivilprozess